Aspek Imunologi Peran Homosistein Dalam Patogenesis Gangguan Kognitif Pasca Stroke Iskemik - Harahap, Herpan Syafii (Jurnal Kedokteran, 2020)
Approximately 70% of acute ischemic stroke patients suffered from cognitive impairment that can be a direct insult of the ischemic stroke itself or as a consequence of the interaction between ischemic stroke event and its associated risk factors. Hyperhomocysteinemia is one of the vascular risk factors which can contribute to the pathophysiology of cognitive impairment after ischemic stroke. This condition can be due to an increase in the SAM / SAH ratio associated with a high methionine-containing diet, genetic predisposition, and deficiency of vitamin B6 and folic acid. The role of homocysteine ??in the pathogenesis of post-stroke cognitive impairment has not yet been studied extensively. Homocysteine ??is toxic and can induce systemic inflammatory responses, disruption of the blood-brain barrier, neuroinflamation, and neuronal death that lead to neurodegenerative processes. Neurodegenerative processes in particular brain structures that carry out certain function of cognitive domains will disrupt the function of those cognitive domains. Understanding the immunological aspects of the role of homocysteine ??in the occurrence of cognitive impairment among ischemic stroke patients is beneficial in providing an opportunity for development of interventions against homocysteine ??and its immunological responses consequences as the part of optimal management of post-ischemic cognitive impairment.